(untitled) (Research, Society and Development, 2021)
The study evaluated the physicochemical and sensory characteristics of loaf Bread with the addition of 0%(FP0), 5%(FP5), 10%(FP10) and 15%(FP15) of forage palm flour, replacing the flour of white wheat. The breads were subjected to sensory analysis by 106(one hundred and six) untrained judges. The FP5 bread was the most accepted, with na acceptability rate of 75%. Analyzes of total phenolic compounds and antioxidant activity were performed by the ABTS•⁺ radical capture method, in FP0 and FP5, however, the analyzed samples did not show statistically significant difference between them by the Tukey test (p<0.05). In FP5, the forage palm flour increased the contento of fiber and micronutrients, such as calcium (Ca), magnesium (Mg), potassium (K), zinc (Zn) and vitamin C, without changing the texturometric parameters (p<0.05). Bread formulated with forage palm flour can be a low-cost aternative to incorporate important nutrients in the human diet, however, it is necessary to carry out studies on the presence of antinutritional factors. Considering the acceptability índex achieved by sliced Bread, incorporation of forage palm flour enables the increase of important micronutrients in the hum dieta t values much higher than the values found in conventionally baked Bread. Although the forage cactus has a green color, this characteristic did not offer resistance to the acceptance of the loaf of Bread by potential consumers of the product and may be attrative to children in the preschool phase.